A New Cavity Classification LOV/DD: An Original Hypothesis - Oleksandr Bulbuk; Olena Bulbuk; Mykola Rozhko (Wolters Kluwer Medknow Publications, 2020)
Introduction: Previous research have established - in the problem solving of diagnosis and treatment of hard tissues defects, a significant role belongs to the choice of tactics treatment tooth destruction. This work aims to study the diagnosis problems and cavity classification, what will facilitate objectification of diagnostic and therapeutic approaches in the dental treatment of patients with this disease. For differential estimation of defects in teeth and for a precise assessment of the strength of the composition "tooth-restoration", we conducted a mechanic-mathematical modeling of contact interaction of restoration with tooth tissues. We also conducted anthropometric studies cavities all kinds and different groups of teeth. The Hypothesis: The first division of the cavities we have conducted in depth lesions: depth of destruction (DD). The next division we conducted on several parameters: Location of defects, Occlusion load, Volume of defects (LOV). As a result of the study, was proposed the cavity classification LOV/DD, is offered the method choice algorithm of treatment hard tissues defects, which is based on classification LOV/DD, and can serve as a selection criterion in the treatment of such pathologies. Evaluation of the Hypothesis: The proposed classification fills the obvious gap in academic representations of hard tissue defects, suggests the prospect of reaching a consensus on differentiated diagnostic and therapeutic approaches in the treatment of patients with this disease.